Performance Monitoring Using Coherent Receivers - Geyer, J.C.; Fludger, C.R.S.; Duthel, T.; Schulien, C.; Schmauß, Bernhard (Optical Fiber Communication 2009, 2009)
We review performance monitoring using data of the digital equalizer of coherent receivers and show simulation and measurement results from 43Gb/s transmission data. © 2009 OSA.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.perfor
Keywords: (060.1660) Coherent communications; (060.2300) Fiber measurements